2015
DOI: 10.1021/acs.macromol.5b02222
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene-Based Hyper-Cross-Linked Polymer Sponge for Gas Storage and Water Treatment

Abstract: Cost-effective adsorbents for water treatment is easy available through one-pot Friedel−Crafts reaction of triptycene. With hierarchical porous structure, high surface area, high thermal stability, and excellent adsorption capacities for organic solvents and dyes, the triptycene-based hyper-cross-linked polymer sponge (THPS) may be ideal adsorbents for a wide range of large-scale applications in water purification and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(119 citation statements)
references
References 55 publications
(42 reference statements)
4
115
0
Order By: Relevance
“…Although CR is an anionic dye, it exhibited the maximum absorption capacity, suggesting the absorption of Fc‐HPP for dyes mainly depends on the size of the dye. The larger molecules could enter and bind in the micropores, whereas small‐sized molecules could easily enter into and out of pores so that Fc‐HPP preferred to absorb large‐sized dyes molecules . Compared with CV, the carboxyl group and one quinone ring in RB could result in relatively weaker electrostatic interaction with Fc‐HPP .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CR is an anionic dye, it exhibited the maximum absorption capacity, suggesting the absorption of Fc‐HPP for dyes mainly depends on the size of the dye. The larger molecules could enter and bind in the micropores, whereas small‐sized molecules could easily enter into and out of pores so that Fc‐HPP preferred to absorb large‐sized dyes molecules . Compared with CV, the carboxyl group and one quinone ring in RB could result in relatively weaker electrostatic interaction with Fc‐HPP .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the color of the solution turned from dark red to pale red, then to nearly colorless, while the Fc‐HPP power became rufescent (as shown in the inset of Figure ). Meanwhile, pseudo‐first‐order and pseudo‐second‐order models served to simulate the absorption performance and the results suggested that the pseudo‐second‐order kinetic model was more favorable to explain the absorption process by comparing the value of R 2 . The fitted curves and correlative kinetic parameters are listed in Figure S7 and Table S3 in the Supporting Information, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Knitting of the triptycene monomer can produce HCPs which show high adsorption for solvents including DMSO, toluene, and ethyl acetate, with a 30 times increase in the mass of the polymer observed for adsorption of chloroform. 44 Functionalised β-cyclodextrins have been used to extract phenol and its derivatives from aqueous solutions. 45 Gold nanoparticles have also been incorporated into hypercrosslinked β-cyclodextrin to facilitate catalytic reactions on the adsorbed materials.…”
Section: Introductionmentioning
confidence: 99%
“…N 2 adsorption–desorption isotherm of Pd/KAPs(DCM‐TPP) at 77 K displayed a typical type І curve along with a large adsorption at low pressure ( P / P 0 < 0.1), which are suggestive of the coexistence of micropores and mesopores in the framework (Figure ) . The Brunauer–Emmett–Teller surface area was found to be 1357 m 2 g −1 .…”
Section: Resultsmentioning
confidence: 97%